From Stage to Heart: K-Pop Concerts and Emotional Attachment in Celebrity Worship - Jasmine Alya Pramesthi (MUKASI: Jurnal Ilmu Komunikasi, 2025)
This study examines the influence of K-Pop Concerts (X1) and Emotional Attachment (X2) on Celebrity Worship (Y) among K-Pop fans using Cultivation theory. This theory explains how intensive exposure, such as concerts, shapes fans' perceptions and attachment to idols. Involving 384 respondents who have attended at least one concert in the past two years, the study found that K-Pop concerts and emotional attachment significantly influence celebrity worship. Collectively, the two variables explained 47.2% of the variance in celebrity worship.  These results suggest that K-Pop concerts provide a direct experience between fans and idols, while emotional attachment plays an important role in strengthening fans' psychological connection with idols. Both independently contribute to the level of celebrity worship, reflecting the intensity of fans' connection with idols that goes beyond mere entertainment.  This research provides strategic insights for the entertainment industry in creating more meaningful experiences to increase fan loyalty. Moreover, the findings enrich the academic literature on fan behavior in the context of global popular culture, by highlighting the relevance of Cultivation theory.